Environmental sustainability of municipal wastewater treatment through struvite precipitation: Influence of operational parameters. (20th February 2021) - Mavhungu, Avhafunani; Foteinis, Spyros; Mbaya, Richard; Masindi, Vhahangwele; Kortidis, Ioannis; Mpenyana-Monyatsi, Lizzy; Chatzisymeon, Efthalia
Abstract: The environmental sustainability of wastewater treatment through phosphate (P) and ammonia (N) chemical precipitation (struvite) was examined using the life cycle assessment methodology. Thermally activated (calcined) cryptocrystalline magnesite was used towards struvite formation and four process parameters (contact time, magnesite dosage, initial wastewater pH and temperature) were studied. Raising wastewater's temperature to promote ammonia stripping was found to be environmentally unsound. Magnesite dosage and contact time were identified as environmental hotspots, but not pH. In terms of environmental relevance, when using ReCiPe 2016 life cycle impact assessment method, the human health damage category was mostly affected, followed by resource availability, while ecosystems category was affected to a much lesser extent. Environmental impacts were grossly attributed to South Africa's fossil fuel-dependent energy mix, suggesting that renewable energy could largely improve the system's environmental performance. The optimal conditions, from the environmental perspective, were found to be 0.2 g L −1 feed dosage and 10 min mixing, at ambient temperature and pH (total environmental footprint 60.9 μPt per treated L of wastewater). To improve N removal efficacy, which is desirable in real-world applications, higher feed dosages and mixing durations are required, albeit at the expense of environmental sustainability (e.g. the 180 min and 16 g L −1 environmental footprint sharply rises to 1.87 mPt L −1 ). The net impact approach revealed that the avoided environmental impacts on the midpoint impact categories freshwater and marine eutrophication grossly outweigh the corresponding environmental impacts of the treatment process. Results suggest that when using a low contact time and magnesite dosage, struvite precipitation could act as a fast, efficient, and environmentally friendly pre-treatment step to practically remove P and grossly reduce N from wastewater. On the other hand, with higher feed dosages and mixing durations, struvite precipitation could act as a promising secondary wastewater treatment method with an overall low environmental footprint. Overall, results complement the existing body of knowledge on the techno-economic performance of such systems and provide insight to decision- and policy-makers to sustainably scale up the process, at village- or industrial-level, in rural South Africa, Lesotho, and further afield. Highlights: The LCA methodology was employed to study struvite crystallisation. Four main process parameter were examined in terms of environmental relevance. Raising wastewater temperature is environmentally unsound. Magnesite dosage and contact time were environmental hotspots. The optimal condition, from the environmental perspective, were identified.